Multiple Fra-1-bound enhancers showing different molecular and functional features can cooperate to repress gene transcription - Fabienne Bejjani; Emilie Evanno; Samantha Mahfoud; Claire Tolza; Kazem Zibara; Marc Piechaczyk; Isabelle Jariel-Encontre (Cell & Bioscience, 2023)
Abstract Background How transcription factors (TFs) down-regulate gene expression remains ill-understood, especially when they bind to multiple enhancers contacting the same gene promoter. In particular, it is not known whether they exert similar or significantly different molecular effects at these enhancers. Results To address this issue, we used a particularly well-suited study model consisting of the down-regulation of the TGFB2 gene by the TF Fra-1 in Fra-1-overexpressing cancer cells, as Fra-1 binds to multiple enhancers interacting with the TGFB2 promoter. We show that Fra-1 does not repress TGFB2 transcription via reducing RNA Pol II recruitment at the gene promoter but by decreasing the formation of its transcription-initiating form. This is associated with complex long-range chromatin interactions implicating multiple molecularly and functionally heterogeneous Fra-1-bound transcriptional enhancers distal to the TGFB2 transcriptional start site. In particular, the latter display differential requirements upon the presence and the activity of the lysine acetyltransferase p300/CBP. Furthermore, the final transcriptional output of the TGFB2 gene seems to depend on a balance between the positive and negative effects of Fra-1 at these enhancers. Conclusion Our work unveils complex molecular mechanisms underlying the repressive actions of Fra-1 on TGFB2 gene expression. This has consequences for our general understanding of the functioning of the ubiquitous transcriptional complex AP-1, of which Fra-1 is the most documented component for prooncogenic activities. In addition, it raises the general question of the heterogeneity of the molecular functions of TFs binding to different enhancers regulating the same gene.